2021
DOI: 10.1002/brb3.2235
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated neuronal and autonomic responses during error processing in anorexia nervosa

Abstract: contributed equally to this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Individuals with AN present with reduced gray matter in the ACC, which is related to severity of the disorder as measured by BMI ( Mühlau et al, 2007 ). fMRI studies have produced conflicting findings, as elevated ACC activity has been reported in one study with female adolescents who have a diagnosis of AN ( Geisler et al, 2017 ), whilst others report no difference in ACC activity in individuals who have either recovered from AN or have a current diagnosis, compared to HCs ( Wierenga et al, 2014 ; Ritschel et al, 2017 ; Suttkus et al, 2021 ). It is worth highlighting that none of these studies used a Flanker task in their designs, instead a probabilistic reversal learning task ( Geisler et al, 2017 ; Ritschel et al, 2017 ), Stop-signal task ( Wierenga et al, 2014 ), and Go/NoGo task ( Suttkus et al, 2021 ) were employed.…”
Section: Executive Functioningmentioning
confidence: 99%
See 2 more Smart Citations
“…Individuals with AN present with reduced gray matter in the ACC, which is related to severity of the disorder as measured by BMI ( Mühlau et al, 2007 ). fMRI studies have produced conflicting findings, as elevated ACC activity has been reported in one study with female adolescents who have a diagnosis of AN ( Geisler et al, 2017 ), whilst others report no difference in ACC activity in individuals who have either recovered from AN or have a current diagnosis, compared to HCs ( Wierenga et al, 2014 ; Ritschel et al, 2017 ; Suttkus et al, 2021 ). It is worth highlighting that none of these studies used a Flanker task in their designs, instead a probabilistic reversal learning task ( Geisler et al, 2017 ; Ritschel et al, 2017 ), Stop-signal task ( Wierenga et al, 2014 ), and Go/NoGo task ( Suttkus et al, 2021 ) were employed.…”
Section: Executive Functioningmentioning
confidence: 99%
“…Compared to OCD, fewer studies have examined response inhibition in AN. Overall, studies either report impairments in response inhibition, including increased error rates and longer reaction times compared to HCs ( Galimberti et al, 2012 ; Collantoni et al, 2016 ), or no differences between individuals with AN and HCs (e.g., Oberndorfer et al, 2011 ; Wierenga et al, 2014 ; Yue et al, 2020 ; Suttkus et al, 2021 ). Response inhibition impairments appear to be more pertinent for individuals with AN-BP eating behaviors ( Galimberti et al, 2012 ), whilst adolescents with AN-R demonstrate enhanced response inhibition compared to HCs ( Weinbach et al, 2020 ).…”
Section: Executive Functioningmentioning
confidence: 99%
See 1 more Smart Citation